PERFORMANCE OF THE PROTOCOL AND LEADERSHIP COMMUNICATION SECTION IN FACILITATING THE AGENDA OF THE HEAD OF THE PASURUAN CITY GOVERNMENT - Hasanah, Abida; Handoko, V. Rudy; Rochim, Achluddin Ibnu (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The formulation of the problem in this study is to ask about the performance and inhibiting factors of the Protocol and Communication Section of the Pasuruan City Leadership in facilitating the agenda of the regional head of the Pasuruan City Regional Government. This study aims to determine and analyze the performance and inhibiting factors of the performance of the Protocol and Communication Section of Pasuruan City Leaders in facilitating the agenda of the head of the Pasuruan City Regional Government. The research method used is a qualitative research method with a descriptive approach. The author collects data qualitatively using interviews, observation, and documentation techniques. The use of this method is expected to describe the phenomena that occur in the collaboration process with the development of the theory that researchers refer to to produce a more comprehensive description of the phenomena. The results of this study show that the Protocol and Communication Section of the Leadership in Pasuruan City achieved very satisfactory individual performance in 2022, with the Percentage of Leadership Needs Services reaching 100%, exceeding the 90% target, Nevertheless, there are obstacles, such as frequent miscommunication. This section is crucial in supporting the Regional Head's agenda, involving event coordination, monitoring readiness, and others. The recommendations to improve the performance of the Protocol and Communication Section are to develop guidelines (SOP), organize training to improve the quality of human resources (HR), and strengthen coordination to ensure mutual understanding of protocol technical policies.